2018
DOI: 10.2147/dddt.s150317
|View full text |Cite
|
Sign up to set email alerts
|

Inotuzumab ozogamicin: a CD22 mAb–drug conjugate for adult relapsed or refractory B-cell precursor acute lymphoblastic leukemia

Abstract: Despite improved rates of remission and cure in newly diagnosed adult acute lymphoblastic leukemia (ALL), the prognosis for patients with relapsed or refractory disease remains poor and the 5-year overall survival rate after relapse is under 10%. A recent paradigm shift has focused on the promise of targeted immunotherapy rather than standard chemotherapy, as ALL blast cells express a variety of antigens, and monoclonal antibodies may be developed to identify and destroy the leukemic cells. Inotuzumab ozogamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…Inotuzumab ozogamicin (InO) is a recently introduced targeted therapy for adults with R/R CD22‐positive B‐cell precursor (BCP) ALL . InO is an antibody‐drug conjugate composed of a humanized anti‐CD22 monoclonal antibody conjugated to the cytotoxic agent calicheamicin .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inotuzumab ozogamicin (InO) is a recently introduced targeted therapy for adults with R/R CD22‐positive B‐cell precursor (BCP) ALL . InO is an antibody‐drug conjugate composed of a humanized anti‐CD22 monoclonal antibody conjugated to the cytotoxic agent calicheamicin .…”
Section: Introductionmentioning
confidence: 99%
“…1,6 Inotuzumab ozogamicin (InO) is a recently introduced targeted therapy for adults with R/R CD22-positive B-cell precursor (BCP) ALL. 7,8 InO is an antibody-drug conjugate composed of a humanized anti-CD22 monoclonal antibody Cancer July 15, 2019 conjugated to the cytotoxic agent calicheamicin. 9,10 It binds with high affinity to CD22, a cell-surface antigen expressed by >90% of B-cell blasts in nearly all patients with B-cell ALL.…”
Section: Introductionmentioning
confidence: 99%
“…However, at high leukemic burden, vascular remodeling results in collapsed vessels, reduced perfusion, and reduced vascular surface area, which lowers K trans back to values similar to those of control mice. Increased K trans values in low burden ALL may indicate a therapeutic window of enhanced delivery for ALL antibody-based therapies such as those targeting CD19 or CD22 which are similar in size to 150 KDa dextran [19,20]. However, differences in vascular transport mechanisms of dextran and therapeutic antibodies make further assessments of antibody delivery kinetics necessary [21].…”
Section: Discussionmentioning
confidence: 99%
“…After targeting CD22 + by InO in ALL blasts, preclinical and phase 1-2 studies showed that antibody ligation was rapidly followed by internalization of the complex into lysosomes, where calicheamicin is released. This drug binds to the DNA groove, leading to double-strand cleavage and subsequent apoptosis [28]. These studies also highlighted that the levels of unconjugated calicheamicin were below the limit of quantitation (50 pg/mL) for most patients and at different time points.…”
Section: Therapeutic Anti-cd22 Antibodies In B-allmentioning
confidence: 92%
“…In a recent single-arm, phase 2 study, InO in combination with low-intensity chemotherapy was used for old patients with Ph-negative ALL [28]. The results showed that InO is active in the disease, with a high proportion of patients achieving MRD negativity and improved survival outcomes.…”
Section: B-all Subgroupsmentioning
confidence: 99%